Human papillomavirus (HPV) genotypes in an Australian sample of anal cancers. Issue 4 (4th February 2014) - Hillman, Richard J.; Garland, Suzanne M.; Gunathilake, Manoji P.W.; Stevens, Matthew; Kumaradevan, Nirmala; Lemech, Charlotte; Ward, Robyn L.; Meagher, Alan; McHugh, Leo; Jin, Fengyi; Carroll, Susan; Goldstein, David; et al.
<x xml:space="preserve">Abstract</x> Human papillomavirus (HPV) causes most cases of anal cancers. In this study, we analyzed biopsy material from 112 patients with anal cancers in Australia for the presence of HPV DNA by the INNO LiPA HPV genotyping assay. There were 82% (92) males and 18% (20) females. The mean age at diagnosis was significantly (p = 0.006) younger for males (52.5 years) than females (66 years). HIV‐infected males were diagnosed at a much earlier mean age (48.2 years) than HIV negative (56.3 years) males (p = 0.05). HPV DNA was detected in 96.4% (108) of cases. HPV type 16 was the commonest, at 75% (81) of samples and being the sole genotype detected in 61% (66). Overall, 79% (85) of cases had at least one genotype targeted by the bivalent HPV (bHPV) vaccine, 90% (97) by the quadrivalent HPV (qHPV) vaccine and 96% (104) by the nonavalent HPV (nHPV) vaccine. The qHPV vaccine, which is now offered to all secondary school students in Australia, may prevent anal cancers in Australia. However, given the mean age of onset of this condition, the vaccine is unlikely to have a significant impact for several decades. Further research is necessary to prove additional protective effects of the nHPV vaccine.